Intensification and forecasting of low-pour-point diesel fuel production via modelling reactor and stabilizer column at industrial unit; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Belinskaya N. S. Natalia Sergeevna; Frantsina E. V. Evgeniya Vladimirovna; Ivanchina E. D. Emilia Dmitrievna; Popova N. V.; Zyryanova I. V.; Averyanova E. V. (Latest Research in Hydrocarbon Refining, 2016)
Title screen